Practitioners' learning about healthcare supply chain management in the COVID-19 pandemic: a public procurement perspective. Issue 13 (9th December 2021) - Harland, Christine Mary; Knight, Louise; Patrucco, Andrea S.; Lynch, Jane; Telgen, Jan; Peters, Esmee; Tátrai, Tünde; Ferk, Petra
Abstract : Purpose: The procurement and supply of crucial healthcare products in the early stages of the COVID-19 emergency were chaotic. To prepare for future crises, we must be able to describe what went wrong, and why, and map out ways to build agility and resilience. How can this be done effectively, given the highly complex and diverse network of actors across governments, care providers and supply chains, and the extreme uncertainty and dynamism in the procurement system and supplier markets? The purpose of this study was to capture learning from practitioners in "real time" in a way that could frame and inform capacity building across healthcare systems with varying procurement and supply management maturity. Design/methodology/approach: This exploratory study involved interviews with 58 senior public procurement practitioners in central and regional governments, NGOs and leaders of professional organizations from 23 countries, very early in the COVID crisis. Following the first, inductive phase of analysis leading to five descriptive dimensions, the awareness-motivation-capability (A-M-C) framework was applied in a further round of coding, to understand immediate challenges faced by procurement practitioners, how the complex, multi-level procurement system that shaped their motivations to respond and critical capabilities required to face these challenges. Findings: Developments across 23 countries and practitioners' learning about procurement and supply in the pandemic crisis can be captured in five overarching themes: governance and organization, knowledge and skills, information systems, regulation and supply base issues. Together these themes cover the strengths and gaps in procurement and supply capability encountered by procurement leaders and front-line personnel. They highlight the various facets of structure, resource and process which constitute organizational capability. However, to account better for the highly dynamic situation characterized by both unprecedented rivalry and cooperation, analysts must also pay attention to actors' emerging awareness of the situation and their rapidly changing motivations. Originality/value: The application of the A-M-C framework is unique in the healthcare supply chain and disaster management literature. It enables a comprehensive overview of healthcare procurement from a system perspective. This study shows how increasing system preparedness for future emergencies depends both on developing critical capabilities and understanding how awareness and motivation influence the effective deployment of those capabilities.